Global Humanism: Possibilities and Risks of a New Humanistic Model (Bodhi: An Interdisciplinary Journal, 2013)
Introduction The world develops terrifically fast: Technologies, media, states... But do humans develop as fast as their inventions? Which effects does the globalization have on the understanding of the individual and humanity? We have to choose between lots of possibilities - thanks to technology and research, but: What should we do now? How should we handle the potential which is available for us? My book „Global Humanism – possibilities and risks of a new humanistic model“ appeared in 2010 and discusses the possibilities and risks of a new, ethical model, a Global Humanism, which puts the individual as a global being in the centre of attention. Humanism is a big idea which everyday life puts to the test. I have recently returned from travels all around the world and to keep your humanistic attitude while travelling is a special challenge. It also showed me the necessity of a global ethical concept, which can apply in a lot of human environments. Nevertheless, the important question to be discussed remains: What can an ethical model like the Global Humanism really perfom? This question caught my interest as a scholar. DOI: http://dx.doi.org/10.3126/bodhi.v6i0.9241 Bodhi Vol.6 2013: 17-20